SPIRITUALITAS RASUL PAULUS DAN RELEVANSINYA BAGI KATEKIS SEBAGAI PEWARTA INJIL - Bahari, Pino; Dewantara, Agustinus Wisnu (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
This study aims to explore the spirituality of the Apostle Paul and its relevance for catechists in carrying out their evangelization mission. Spirituality is a crucial aspect for evangelists of Jesus Christ, as it strengthens their ability to fulfill their missionary duties. Catechists, as heralds and servants in the life and development of the Church, are experiencing a decline in spirituality, which affects their dedication and enthusiasm in ministry. Many catechists serve merely as a duty rather than as a true calling, leading to a lack of commitment, discouragement, arrogance, and diminished enthusiasm. This research is conducted using a qualitative approach through library research by collecting and analyzing various relevant published sources, including books, journals, articles, scientific works, the Bible, and online resources. The research method involves data collection through documentation techniques, followed by data analysis through data reduction and data display, and finally drawing conclusions from the collected data. The findings indicate that the spiritual values of the Apostle Paul hold significant relevance for catechists today, providing guidance and inspiration to strengthen their commitment and spiritual resilience in preaching the Gospel.